DEFINING THE ROLE OF THE EU AS A GLOBAL ACTOR: CHALLENGES AND PERSPECTIVES - Vasko Naumovski, Milena Apostolovska Stepanoska, Leposava Ogjnanovska (Konrad Adenauer Foundation, Republic of North Macedonia / Institute for Democracy “Societas Civilis”, Skopje, 2021)
The Union’s internal cohesion is key to the effectiveness of European responses and dealing with global crises. The EU institutions and the member states must establish a common vision that would be realized through strong coordination structures for harmonization of action and adoption of appropriate measures for increased visibility in the modern international system. The concept of the EU as a global actor that relies primarily on its soft power is a concept that belongs to the past, as it cannot provide a sufficient international presence in proportion to the size of the Union. The EU as a global power with combined power characteristics is a more appropriate concept to achieve the ambitions for influence on the international scene.
Keywords: European Union, Globalism, Western Balkans, Enlargement